Vitamin D Deficiency and Metabolism in HIV-Infected and HIV-Uninfected Men in the Multicenter AIDS Cohort Study - Zhang, Long (AIDS Res Hum Retroviruses, 2017)
We evaluated associations of serum 25-hydroxyvitamin D (25[OH]D) and 1,25-dihydroxyvitamin D (1,25[OH](2)D) levels in a cohort of HIV-infected and HIV-uninfected men at risk for infection in the United States. Stored samples collected between 1999 and 2008 were tested for vitamin D metabolites between 2014 and 2015. Vitamin D deficiency was defined as a serum concentration of 25[OH]D <20 ng/ml. Multivariate models were used to assess associations of various demographic and clinical factors with vitamin D status. HIV-infected men on effective antiretroviral therapy (n = 640) and HIV-uninfected men (n = 99) had comparable levels of 25[OH]D and 1,25[OH](2)D, and prevalences of vitamin D deficiency were 41% in HIV-infected and 44% in HIV-uninfected men, respectively. Self-reported black or other non-white race, obesity, and normal kidney function were significant predictors of vitamin D deficiency regardless of HIV serostatus. Lower CD4(+) T cell count was associated with vitamin D deficiency in HIV-infected men, while current ritonavir use was protective. Self-reported black race was the only factor significantly associated with higher levels of 1,25[OH](2)D (vs. whites; β = 4.85 pg/ml, p = .003). Levels of 1,25[OH](2)D and 25[OH]D were positively correlated in HIV-infected men (β = 0.32 pg/ml, p < .001), but not in uninfected men (β = −0.09 pg/ml, p = .623; p < .05 for interaction). Vitamin D deficiency was prevalent regardless of HIV serostatus in this cohort, suggesting that HIV infection did not confer additional risk of deficiency in this cohort of well-treated HIV-infected men. However, HIV infection and race may have implications for vitamin D metabolism and 1,25[OH](2)D levels.